1995
DOI: 10.1103/physrevd.52.1212
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous chiral-symmetry breaking in three-dimensional QED with a Chern-Simons term

Abstract: In three-dimensional $ED with a Chern-Simons term we study the phase structure associated with chiral-symmetry breaking in the framework of the Schwinger-Dyson equation. We give detailed analyses on the analytical and numerical solutions for the Schwinger-Dyson equation of the fermion propagator, where the nonlocal gauge-fixing procedure is adopted to avoid wave-function reriormalization for the fermion. In the absence of the Chern-Simons term, there exists a finite critical number of four-component fermion fl… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
41
0

Year Published

1996
1996
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(45 citation statements)
references
References 48 publications
4
41
0
Order By: Relevance
“…At finite temperature QED 3 , there still exists a critical fermion flavor, which will be reduced by the temperature increasing. [24][25][26][27][28] In the nonlocal gauge, [9][10][11][29][30][31][32][33] the gauge parameter ξ is dependent on the momentum or coordinates, while in the usual R ξ gauge, ξ is just a constant. The nonlocal gauge can be transformed into the Landau gauge by the inverse LKFT.…”
Section: Introductionmentioning
confidence: 99%
“…At finite temperature QED 3 , there still exists a critical fermion flavor, which will be reduced by the temperature increasing. [24][25][26][27][28] In the nonlocal gauge, [9][10][11][29][30][31][32][33] the gauge parameter ξ is dependent on the momentum or coordinates, while in the usual R ξ gauge, ξ is just a constant. The nonlocal gauge can be transformed into the Landau gauge by the inverse LKFT.…”
Section: Introductionmentioning
confidence: 99%
“…It has many features similar to quantum chromodynamics (QCD), such as spontaneous chiral symmetry breaking in the massless fermion limit and confinement [1][2][3][4][5][6][7][8][9][10][11][12][13]. Moreover, it is super-renormalizable, so it does not suffer from the ultraviolet divergence which are present in QED 4 .…”
Section: Introductionmentioning
confidence: 99%
“…When studying DCSB in QED 3 , one has to use four-component fermions with γ matrices [5][6][7][8][9][10][11][12][13][14], since the model with two-component fermions with Pauli matrices does not have chiral properties due to the property of Pauli matrix algebra. On the other hand, Chern-Simons theory has induced many significative studies in QED 3 [15][16][17][18]. Besides introducing Chern-Simons term into the normal QED 3 Lagrangian, it was also found that in QED 3 with two-component fermions a Chern-Simons like term can also be induced from radiative corrections [19][20][21][22][23][24][25] (Appendix A).…”
mentioning
confidence: 99%